Modeling cadmium exposures in low- and high-exposure areas in Thailand - Soisungwan Satarug (2018)
Background: Previous U.S. population modeling studies have reported that urinary cadmium (Cd) excretion patterns differ with age, sex, and dietary exposure; associations between Cd exposures and health outcomes also have differed by age and sex. Therefore, it is important to test models used to estimate Cd exposures across an expanded Cd-exposure range. Objectives: We estimated relative Cd exposures from both diet and smoking in low- and high-exposure scenarios to provide data for improving risk assessment calculations. Methods: We used a Cd toxicokinetic-based model to estimate Cd exposures based on urinary Cd levels measured for 399 persons in a low-exposure area (Bangkok) and 6,747 persons in a high-exposure area (Mae Sot) in Thailand. Results: In Bangkok, we estimated dietary Cd exposures of 50-56 μg/day for males and 21-27 μg/day for females 20-59 years of age who never smoked. In Mae Sot, we estimated dietary Cd exposures of 188-224 μg/day for males and 99-113 μg/day for females 20-59 years of age who never smoked. In Bangkok, we estimated Cd exposures from smoking to be 5.5-20.4 μg/day for male smokers 20-59 years of age. In Mae Sot, we estimated Cd exposures from smoking to be 9.8-26 μg/day for male heavy smokers and 26 μg/day for female heavy smokers. Conclusion: This study provides estimates of Cd exposures from diet and smoking in low- and high-exposure scenarios. Our findings suggest a relatively small safety margin between the established tolerable Cd reference exposure of 62 μg/day and exposure levels previously associated with evidence of kidney and bone effects in Mae Sot residents, where dietary Cd exposures among women were only 1.6-2.1 times the reference value.